(untitled) (Global Journal of Management and Business Research, 2014)
Entrepreneurship is vital for economic growth in Oman and college students play a significant role in enriching entrepreneurship industry. The aim of this paper is to investigate the entrepreneurial intention among Information Systems (IS) students in Oman with relations to their entrepreneurship education and government and private sector supportive programs. Data was collected from two focus groups of IS students in Sultan Qaboos University. Data was analyzed using thematic analysis. The results revealed that the majority of IS students have low entrepreneurial intention, the main factors that have positive impact on students’ entrepreneurial intention are money, independence, and work flexibility, the lack of entrepreneurship courses in IS department impacts students’ entrepreneurial intention negatively, and Omani students are not well educated about the supportive programs provided by the government and private sector for entrepreneurs.